Osoby o zadeklarowanym różnym stopniu religijności, a korzystanie z internetowych mediów chrześcijańskich, w tym misyjnych, w Polsce. Badania pastoralno-prasoznawcze - Wrzos , Marcin (Annales Missiologici Posnanienses, 2020)
Media communicating via the Internet have become tools of evangelizing influence since the early 1990s. They became the subject of research for the author, in terms of how well they are known to the Internet users depending on the degree of religiosity they declared (believers and regular users, believers and occasional practitioners, non-believers), which allowed to formulate pastoral postulates and conclusions. The survey included persons from a representative, nationwide sample (N = 1000) who completed standardized CAWI (Computer-Assisted Web Interview) questionnaire interviews and VIDI (Virtual Individual In-Depth Interviews – individual indepth interviews). This is the first such extensive research on Poland. According to the research, the knowledge and use of Christian media that communicate through the Internet, including the missionary ones, changes depending on the respondents’ declared degree of religiosity.